Contamination of Polynuclear Aromatic Hydrocarbons- (PNAH) in Sediments: Identification And Distribution in the River of Shatt Al-Arab-(ROSA) - Wisam Abdul-Ameer Farid1 , Wasen Abdul-Ameer Ali1 , Aseel Nadum Al-Salman2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The sediments were analyzed for total organic carbon content-(TOCC), grain size-(GS), and PNAH levelsand origins. The sediments were taken from 9 stations-(ST) on ROSA. Gas chromatography-(GC) analysisshowed that the PNAH level in ROSA sediments was comparatively low to medium compared to otherworld locations. The PNAH total levels varied from 31.86 ng/g dry weight-(DW)-(ST 9) to 88.99 ng/g DW-(ST 6). The highest PNAH levels were close to oil pollution sources at ST 2, 4, 6, and 8. The TOCC rangedfrom 0.32 % to 1.64 %. The data suggested that the PNAH levels in the ROSA were linked to TOCC and GS.The PNAH compounds and ratios and analysis of principal components-(AOPC) indicated that the PNAHsources in the river were biogenic-(organisms), pyrogenic-(combustion), and petrogenic-(petroleum).Ecological risk evaluation showed that PNAH did not cause any deleterious impacts on the ROSA.